Blood and rage : a cultural history of terrorism - Burleigh, Michael, 1955- (New York : Harper, 2009)
This book is a sweeping and deeply penetrating work of history that explores the nature of terrorism from its origins in the West to today's global threat fueled by fundamentalists. The author, a distinguished historian emphasizes the lethal resentments and the twisted morality that spawn terrorism rather than the ideological or religious justification that routinely accompanies it. He reveals who the terrorist groups are, how they organize and operate, what motivates their violence, and how wider support encourages them. This book takes us from the roots of terrorism in the Irish Republican Brotherhood, the Russian Nihilists, and the London-based anarchists of Black International to the various terrorist campaigns that exist today. It also explores the lives of people engaged in careers of political violence and those who are most affected by terrorism.
Green : the Fenian dynamiters -- Red : Russian nihilists and revolutionaries -- Black : anarchists and terrorism -- Death in the sun : terror and decolonisation -- Attention-seeking : Black September and international terrorism -- Guilty white kids : the Red Brigades and the Red Army faction -- Small-nation terror -- World rage : Islamist terrorism.
Originally published: London : HarperPress, c2008.
Includes bibliographical references (p. 533-545) and index.
Keywords: Terrorism -- History